(untitled) (Medical Forum Monthly, 2024)
Objective: To study the Priority of Spinal versus general anesthesia for Caesarian-Section In the eyes of gynecologist and patient in Islam Teaching Hospital Sialkot, Shahina Jamil Hospital Abbottabad and CMH Mangla. Study Design: Retrospective study. Place and Duration of Study: This study was carried out at the Islam Teaching Hospital Sialkot, Shahina Jamil Teaching Hospital Abbottabad and CMH Mangla from 1st January 2010 to 28 Feb 2014. Materials and Methods: 250 cases each for Caesarian Section were taken from government hospitals and private hospitals these were analyzed for type of anesthesia with its preference in the eyes of gynecologists and patients. Fully informed written consent had already been taken for type of anesthesia. Permission was also taken from authorities of above mentioned hospitals for the study. Results: In government hospitals the gynecologist preferred (74%) spinal anesthesia for Cesarion section as compared to private hospitals where he/she preferred general anesthesia (85.6 %). Conclusion: It was concluded that the Gynaecologist in the government sector prefers spinal Anesthesia for Caesarian Section but in private practice she / he prefers general anesthesia for Caesarian section. It was seen that the religious women prefer general anesthesia for caesarian section due to modesty reasons but women of modern society listen to the counseling for spinal anesthesia with open mind. The Anesthetist preferred spinal anesthesia for Caesarian section in most of the cases.